Use of supplemental nutritional assistance program benefits by unemployment insurance applicants in Michigan during the Great Recession - Christopher J. O'Leary; Kenneth J. Kline (W.E. Upjohn Institute for Employment Research, 2014)
During the Great Recession, both the Supplementary Nutrition Assistance Program (SNAP) and the federal-state unemployment insurance (UI) program experienced dramatic increases in participation. Using Michigan program administrative data on all SNAP (2006-2011) recipients and all UI (2001-2010) applicants, we examine SNAP use before and after UI application. Both past and future receipts of SNAP are highly negatively correlated with meeting UI income and job separation eligibility requirements. Unemployment insurance applicants with insufficient wage credits or job separations because of quitting or employer discharge are much more likely to have received SNAP in the past. Furthermore, such UI applicants are also more likely to receive SNAP soon after applying for UI benefits. The data also indicate that as of the start of the Great Recession, UI applicants who received SNAP subsequent to UI filing began receiving those benefits sooner compared with UI applicants prior to the downturn. The models also suggest that SNAP receipt after UI application was higher among ineligible UI applicants, applicants who quit or were fired from prior jobs, those with prior recent SNAP receipt, prime age workers, females, those with education of less than a high school diploma, those having three to five years' prior job tenure, and those with a separating job in retail trade, health care, or hospitality.
Keywords: J65; I38; 330; Unemployment insurance; food stamps; supplemental nutrition assistance program; job loss; self sufficiency; economic security; safety net